(untitled) (Journal of the College of Basic Education, 2024)
Proverbs have captivated researchers worldwide, since they mirror how cultures portrait folks’ social lives. African American proverbs related to racism and anti-blackness, among them, are made use of to expose how the culture of the Western world in general and of America in particular view racial attitudes in these sayings. By exploiting four analytical tools of critical stylistics viewed in Jeffries’ model, thirty proverbs will be examined (exemplified by five proverbs) regarding their stylistic features and racial-related ideologies. This paper schemes into how Indians are stereotyped in these proverbs. Through exploiting the selected critical stylistic tools, it concludes that the proverbs examined either implicitly or explicitly express how black people are treated racially and inhumanely in everyday settings and in proverbs as well.